Therapeutic Advancements Across Clinical Stages in Melanoma, With a Focus on Targeted Immunotherapy - Trojaniello, Claudia; Luke, Jason J.; Ascierto, Paolo A. (Frontiers in Oncology, 2021)
Melanoma is the most fatal skin cancer. In the early stages, it can be safely treated with surgery alone. However, since 2011, there was an important revolution in the treatment of melanoma with new effective treatments. Targeted therapy and immunotherapy with checkpoint inhibitors changed the history this disease. To date, more than half of advanced melanoma patients are alive at 5 years; despite this breakthrough, approximately half of the patients still do not respond to treatment. For these reasons, new therapeutic strategies are required to expand the number of patients who can benefit from immunotherapy or combination with targeted therapy. Current research aims at preventing primary and acquired resistance, which are responsible for treatment failure in about 50% of patients. This could increase the effectiveness of available drugs and allow evaluation of new combinations and new targets. The main pathways and molecules under study are: IDO inhibitor, TLR9 agonist, STING, LAG-3, TIM-3, HDAC inhibitors, pegylated IL-2 (NKTR-214), GITR, adenosine pathway inhibitors, among others (there are currently about 3000 trials that are evaluating immunotherapeutic combinations in different tumors). Other promising strategies are cancer vaccines and oncolytic viruses. Another approach is to isolate and remove immune cells (DCs, T cells and NK cells) from the patient's blood or tumor infiltrates, add specific gene fragments, expand them in culture with growth factors, and re-inoculate into the same patient. TILs, TCR gene transfer and CAR-T therapy follow this approach. In this article, we give an overview about the current status of melanoma therapies, the clinical rationale for choosing treatments, and the new immunotherapy approaches.